HLA Matching in Pediatric Kidney Transplantation: HLA Poorly Matched Living Donor Transplants Versus HLA Well-Matched Deceased Donor Transplants. Issue 11 (November 2017) - Opelz, Gerhard; Döhler, Bernd; Middleton, Derek; Süsal, Caner
Abstract : Background: Based on an analysis of 542 pediatric kidney transplants recorded by the UK Transplant Registry from 2000 to 2012, it was concluded that the survival rate of HLA poorly matched living donor transplants is not inferior to that of HLA well-matched deceased donor transplants. Methods: We analyzed the impact of HLA matching on kidney graft survival in 3627 pediatric living donor transplants performed during 2000 to 2015 using the data of the Collaborative Transplant Study. The impact of HLA mismatches on graft survival was analyzed and survival rates of transplants from poorly matched living donors were compared with those from well-matched deceased donors. Multivariate Cox regression analysis was used to account for the influence of confounders. Results: HLA matching had a statistically significant impact on graft survival of pediatric kidney transplants ( P < 0.001). Ten-year graft survival of pediatric transplants from living donors with 4 to 6 HLA-A+B+DR mismatches was significantly worse than that of transplants from well-matched deceased donors with 0 to 1 HLA mismatch (log rank, P = 0.006). Conclusions: In pediatric kidney transplantation, graft survival of kidneys from deceased donors with 0 to 1 HLA mismatches compares favorably with that of grafts from living donors with 4 to 6 HLA mismatches. If possible, living donor pediatric kidney transplants should be performed from donors with fewer than 4 HLA-A+B+DR mismatches. Abstract : In this registry analysis, pediatric kidney graft survival of well HLA matched kidneys from deceased donors compares favorably with that of grafts from poorly HLA matched living donors, increasing the debate over counselling and allocation policies. Supplemental digital content is available in the text.